Corporate social responsibility in the management of Norwegian government pension fund global - Fiedorczuk, Julita (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
This article is an attempt to analysis socially responsible activities in the GPFG with reference to the specifics of the Norwegian economy. For this task was used the self-created tool dividing the dimensions of the concept of CSR and proposing suitable measurement methods for each of them. The phenomenal economic system in Norway (Scandinavian model, welfare state, egalitarianism, sustainable development) has a material impact on the quality and effectiveness of realisation responsible investment in the fund. The findings of the research can be used as a basis for more advanced analysing in other articles.